2007
DOI: 10.1111/j.1708-8240.2007.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Side Effects and Patients’ Perceptions during Tooth Bleaching

Abstract: The experimental HP bleaching solutions, as described in this study, can be used in NGVB with no long-term side effects as evaluated in this study for up to 10 months post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 18 publications
2
23
0
7
Order By: Relevance
“…12,30,32 In the current study, hypersensitivity and gingival irritation were minor and disappeared spontaneously without requiring an interruption of the treatment.…”
Section: Gingival Irritationmentioning
confidence: 87%
“…12,30,32 In the current study, hypersensitivity and gingival irritation were minor and disappeared spontaneously without requiring an interruption of the treatment.…”
Section: Gingival Irritationmentioning
confidence: 87%
“…1,4,9,10,12,13,21 The most common side effects are tooth hypersensitivity and gingival irritation. 1,10,28 These effects are correlated with several factors, such as pH and the peroxide concentration of the bleaching gel, the number and length of applications, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[5][6][7][8] The evaluation of the efficacy and safety of bleaching systems has recieved considerable attention. 1,4,9,10 Although generally positive results have been reported concerning the whitening ability of these agents, concerns still remain as to their effects on periodontal tissues. 11,12 Since their use, significant controversy has been generated regarding the risk of tissue damage from the contact of bleaching agents with the oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Although this adverse effect is usually considered temporary and moderate, it can produce considerable discomfort to the patient [5]. A current study demonstrated that the degree of pulp damage caused by a bleaching gel with a high concentration of hydrogen peroxide (HP) depends on the thickness of enamel and dentin [6].…”
Section: Introductionmentioning
confidence: 85%